An underwater glider for subsea intervention: A technical feasibility study - bin Ibrahim, M.F. (2013)
An underwater glider is a type of autonomous underwater vehicle that moves based on small changes in its buoyancy, maneuvering using it wings as it glides through the water. These gliders, currently used in oceanographic sampling, may potentially be used to deliver payloads for subsea intervention at a lower net transport economy (NTE). Net transport economy, is a measure of the cost of transport in terms of the energy consumed per meter traveled, for each kilogram of loaded mass in air or net buoyancy underwater. The current method of payload delivery is either by using customized support vessel or remotely operated vehicle. This paper presents a technical feasibility study of extending the use of these gliders for subsea intervention, with emphasis on payload delivery. Important aspects of an underwater glider such as its volume (size), speed, wing area, wing span, operational depth and net transport economy were considered. The analysis was based on mathematical models governing existing gliders such as legacy gliders and the XRAY Liberdade. The results obtained were validated by extrapolating the present state of the art in underwater gliders to the proposed future use of these gliders, which is for payload delivery. In conclusion, the use of underwater gliders for subsea intervention is feasible based on factors considered in this study. Â© (2013) Trans Tech Publications, Switzerland.